(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The calculation of activation energy of water groups embedded in the skeleton of sodium tungstate dihydrate, after their being released from normal lattice sites, has been presented by assuming Maxwell Boltzmann distribution of energies among the different water groups, at their characteristic temperature of release. The characteristic temperature has been assumed to be the one at which current versus timetemperature peak starts just building up.These is strong logic behind the assumption that H+ and OH- ions created due to the dissociation of a fraction of total water groups released within the lattice of a hydrated compound may remain in the skeleton through a loose hydrogen bonding. Such H+ and OH– ions would definitely take some finite time for diffusion within the skeleton and thus the crest of the current versus time plot may occur after some finite time of few minutes as observed in Fig. 4.2 for the case of sodium tungstate dihydrate.